2008
DOI: 10.1093/ndt/gfn026
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy with cinacalcet and low doses of vitamin D sterols in patients with moderate to severe secondary hyperparathyroidism

Abstract: Among subjects with moderate to severe sHPT undergoing haemodialysis, combined therapy with cinacalcet and low doses of vitamin D sterols improved achievement of the biochemical targets for CKD-MBD recommended by the KDOQI guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 20 publications
7
81
0
3
Order By: Relevance
“…In addition, it supports studies that have shown that cinacalcet has no clinically relevant interaction with standard immunosuppressive drugs (53). The most frequently reported treatmentemergent AE in the cinacalcet group was diarrhea, similar to what has been reported in other CKD cohorts (7,9,21,54). Previously, concerns have been raised about decreases in renal function following cinacalcet therapy for the treatment of persistent HPT including limited, but significant drops in eGFR (29).…”
Section: Evenepoel Et Alsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, it supports studies that have shown that cinacalcet has no clinically relevant interaction with standard immunosuppressive drugs (53). The most frequently reported treatmentemergent AE in the cinacalcet group was diarrhea, similar to what has been reported in other CKD cohorts (7,9,21,54). Previously, concerns have been raised about decreases in renal function following cinacalcet therapy for the treatment of persistent HPT including limited, but significant drops in eGFR (29).…”
Section: Evenepoel Et Alsupporting
confidence: 84%
“…These morphological transformations are associated with down-regulation of the vitamin D receptor and calcium-sensing receptor (CaSR), which result in parathyroid gland resistance to inhibitory feedback mechanisms (6). Successful renal transplantation corrects the physiologic and metabolic abnormalities responsible for the pathogenesis of secondary HPT (7)(8)(9). However, while endorgan resistance to the action of PTH rapidly wanes parallel to the recovery of renal function, regression of parathyroid gland hyperplasia is uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…In the openlabel TARGET study, 444 haemodialyis patients were treated with cinacalcet and around 80% of the patients were on vitamin D treatment, which was reduced in the second part of the study [11]. Cinacalcet plus low-dose vitamin D treatment was able to improve KDOQI targets [11].…”
Section: Studies Of Cinacalcet In Dialysis Patients With Shptmentioning
confidence: 99%
“…In the openlabel TARGET study, 444 haemodialyis patients were treated with cinacalcet and around 80% of the patients were on vitamin D treatment, which was reduced in the second part of the study [11]. Cinacalcet plus low-dose vitamin D treatment was able to improve KDOQI targets [11]. Another study investigated the combination of cinacalcet with a fixed low-dose vitamin D therapy versus Moe et al [7] Retrospective analysis of outcome parameters in four double-blind randomized studies in 697 dialysis patients with sHPT and cinacalcet plus standard therapy over 12 months (vs. 487 standard therapy only)…”
Section: Studies Of Cinacalcet In Dialysis Patients With Shptmentioning
confidence: 99%
“…All clinical trials concluded that cinacalcet is effective in reducing PTH while simultaneously lowering Ca, P and CaxP levels in HD patients Goodman et al, 2002;Lindberg et al, 2005;Quarles et al, 2003). All these effects could facilitate achievement of the K/DOQI recommended targets (Block et al, 2008;Messa et al, 2008;Moe et al, 2005). Given the difficulty of achieving K/DOQI targets, and the absence of treatment algorithms that take into account both drug treatment (conventional drugs like phosphate binders, and new drugs like paricalcitol and cinacalcet) and HD features, such as the length of dialysis session or the dialysate Ca concentration recommended, our HD Unit has, since 2006, implemented a new treatment protocol for controlling bone metabolism parameters.…”
mentioning
confidence: 99%